Image Scheduling using Cloud Energy Data Computational Techniques - et. al., Dharamvir, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In proposed research Paper we are classifying the process of data intensive business and image scheduling through data computational techniques. The process of Image scheduling computing are having an advantage of tracking data from all available image using data computational specification. In such a domain, computing, data stockpiling and image transformation changes into a utility. It is a sensible form of computing which allow image data for optimal cost of processing operations as in task distribution specification. Since, the classification of present industry are increasing the efficiency of computing was not the aim; instead the goal was to facilitate faster computing by packing more power of computational hardware in form of distributed computing, grids architecture, parallel computing and cloud image transformation . Thereby, the power consumption of such high performance computing architectures lead to increase of power usages and heat which is accompanied by equal amount of energy. Similarly we are going to develop Image scheduling data transformation to achieve required goals